Simple Preparation of the CuO•Fe3O4/Silica Composite from Rice Husk for Enhancing Fenton-Like Catalytic Degradation of Tartrazine in a Wide pH Range - Khanh Huyen Pham Ngoc; Anh-Tuan Vu (Adsorption Science & Technology)
SiO2 was prepared from rice husk (RH) with the assistance of cetrimonium bromide (CTAB), and the CuO•Fe3O4/SiO2 composite was prepared by a simple coprecipitation method to enhance the Fenton-like degradation of dyes in a wide pH range. SiO2 was a mesoporous material with a relatively large surface area of 496.4 m2/g and a highly relative pore volume of 1.154 cm3/g. The Fe3O4 and CuO particles with the size of 20–50 nm were well dispersed in the composite, making the composite tighter and causing the disappearance of large pores in the range of 20–55 nm. The surface area and pore volume of the composite were reduced to 248.6 m2/g and 0.420 cm3/g, respectively. Fe3O4/SiO2 and Fe3O4 samples only exhibited high catalytic activity in an acidic medium, while the CuO•Fe3O4/SiO2 composite could effectively work in a wide pH range of 3–7. Besides, the effects of reaction conditions such as catalyst dosage, H2O2 concentration, and initial dye concentration on the catalytic performance of the composite were studied. The optimal conditions for the degradation of dye were tartrazine (TA) concentration of 50 mg/L, dosage catalyst of 0.5 g/L, H2O2 concentration of 120 mM, and pH 5. The CuO•Fe3O4/SiO2 composite reached the highest activity at pH 5, showing a degradation efficiency (DE) of 93.3% and a reaction rate of 0.061 min−1. The reusability of the catalyst was investigated by cyclic experiments. The DE of the 3rd reuse remained at 55.1%, equivalent to 93.5% of the first use. The catalytic mechanism for the Fenton system has also been proposed.